Organ Procurement Processes in the Operating Room: The Effects of an Educational Session on Levels of Confidence and Understanding in Operating Room Registered Nurses and Surgical Technologists - Ross, Ann; Reilly, Janet; Halla, Emily; Anderson, Kathryn (Operating Room Nurses Association of Canada Journal, 2024)
Objectives: This project aimed to determine the effects an online educational course about organ procurement procedures (OPPs) in the operating room (OR) had on the levels of confidence and understanding among OR registered nurses (RNs) and surgical technologists (STs). Sample and setting: Data was collected from OR RNs and STs in the United States (US) at a Level II trauma centre with 19 operating rooms that completes eight to ten OPPs per year. A graduate nursing leadership student in this hospital created a Microsoft PowerPoint educational course about OPPs as her capstone project. Methods and variables: The course was developed and offered through the online learning management system the hospital uses. A retrospective pretest– posttest survey was designed and evaluated the effects of the course on participants’ levels of confidence and understanding. Results: The overall levels of understanding and confidence about OPPs improved in the RNs and STs, comparing aggregate scores. Implications for perioperative nursing: An educational course can enhance understanding of and confidence in OPPs for OR RNs and STs. Increased confidence and understanding can advance the successful outcomes of the OPPs. Ongoing education is needed to reinforce confidence and understanding in rarely done surgical procedures like OPPs.